Effect of superconducting magnet structure on quench characteristics - Gao, Lianxue; Zhang, Ran; Xu, Mingqing (Australian journal of electrical & electronics engineering, 2021)
In the design process of MRI magnets, the study of quench phenomenon is of great significance to the operation of superconducting magnets. In this paper, the quench characteristics of 1 T symmetric magnet and asymmetric magnet are simulated and analysed by using three-dimensional finite element software OPERA. The modelling process and algorithm of simulation are introduced in detail. The critical current density of NbTi superconducting material is set by looking up table variables preset by software. Through simulation and analysis, the changing principles of the current and resistance of the superconductor coil, which are important physical quantities of the two kinds of magnet structures in quenching are obtained. Three-dimensional simulation graphics are more conducive to observing the propagation speed of quench in different directions. It is concluded that although the DSV (diameter sphere volume) of asymmetric magnet is larger than that of symmetric magnet, the damage of asymmetric magnet is more serious than that of symmetric magnet during the quench.